The Value of Local Leadership of Jero Siraga Figures as a Source of Character Education Based on Sasak Culture - M Zainul Hafizi; Zihori Maulida (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Jurai Siwo Lampung, 2026)
This study is grounded in the growing need to strengthen character education rooted in local cultural values amid the challenges of globalization that threaten the moral identity of younger generations. The Babad Sakra, a traditional Sasak manuscript, presents the story of Jero Siraga, a local leader whose life embodies ethical integrity, social responsibility, and moral courage. This research aims to explore the leadership values represented by Jero Siraga and analyze their relevance as a source for culture-based character education within the Sasak context. Using a qualitative method with an ethnopedagogical approach, the study employed content analysis of the Babad Sakra and interviews with local community figures in Surabaya Village, East Lombok. The findings reveal that Jero Siraga’s transformation from loyalty to political power toward moral devotion to his people reflects the essence of ethical leadership. Core values such as gawe patut (righteousness), gawe berani (moral courage), and gawe luhur (sacrifice for truth) demonstrate strong pedagogical potential for integration into culturally based Social Studies education. The study concludes that the story of Jero Siraga serves not only as a historical narrative but also as a living pedagogical source for nurturing Indonesian students with integrity, empathy, and a deep sense of moral responsibility.